(untitled) (Bangabandhu Sheikh Mujib Medical University Journal, 2018)
This article has no abstract. The first 100 words appear below: A 34 week preterm baby was admitted with the complaints of respiratory distress soon after birth. The mother had bad obstetric history. She is having the fifth gravida with the first two alive and healthy who were born by the normal vaginal delivery at home. The third child was born with severe jaundice and was treated by exchange transfusion. Subsequently the baby developed bilirubin encephalopathy. Then the baby developed cerebral palsy and ultimately died due to aspiration pneumonia at the age of 2.5 years. Her first three pregnancies were not on any antenatal check-up by the health care provider due to poor socio-economic background and illiteracy.